Association between NOx exposure and deaths caused by respiratory diseases in a medium-sized Brazilian city - Cesar, A. C. G.; Carvalho, J. A. [UNESP]; Nascimento, L. F. C. [UNESP] (Assoc Bras Divulg Cientifica, 2015)
Exposure to nitrogen oxides (NOx) emitted by burning fossil fuels has been associated with respiratory diseases. We aimed to estimate the effects of NOx exposure on mortality owing to respiratory diseases in residents of Taubate, Sao Paulo, Brazil, of all ages and both sexes. This time-series ecological study from August 1, 2011 to July 31, 2012 used information on deaths caused by respiratory diseases obtained from the Health Department of Taubate. Estimated daily levels of pollutants (NOx, particulate matter, ozone, carbon monoxide) were obtained from the Centro de Previsao de Tempo e Estudos Climaticos Coupled Aerosol and Tracer Transport model to the Brazilian developments on the Regional Atmospheric Modeling System. These environmental variables were used to adjust the multipollutant model for apparent temperature. To estimate association between hospitalizations owing to asthma and air pollutants, generalized additive Poisson regression models were developed, with lags as much as 5 days. There were 385 deaths with a daily mean (+/- SD) of 1.05 +/- 1.03 (range: 0-5). Exposure to NOx was significantly associated with mortality owing to respiratory diseases: relative risk (RR)=1.035 (95% confidence interval [CI]: 1.008-1.063) for lag 2, RR=1.064 (95% CI: 1.017-1.112) lag 3, RR=1.055 (95% CI: 1.025-1.085) lag 4, and RR=1.042 (95% CI: 1.010-1.076) lag 5. A 3 mu g/m(3) reduction in NOx concentration resulted in a decrease of 10-18 percentage points in risk of death caused by respiratory diseases. Even at NOx concentrations below the acceptable standard, there is association with deaths caused by respiratory diseases.
Keywords: Air pollution; Nitrogen oxides; Respiratory diseases; Death